Aluminum electrolytic capacitor capable of reducing ESR and preparation method thereof
By using a specific chemical liquid to form a dense oxide film in the aluminum electrolytic capacitor, the existing aluminum electrolytic capacitors have solved the problems of high ESR value and low capacitance capacity, and more efficient capacitor preparation and performance improvement are achieved.
Patent Information
- Application Number
- CN202411831954.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The ESR value of existing aluminum electrolytic capacitors is relatively large and the capacitance is relatively low, which cannot meet the demands of increasingly advanced electronic and electrical equipment.
A specific chemical liquid is used, including diates, silane coupling agents containing 3 to 17 fluorine atoms, and fluorine-containing non-ionic surfactant. Through the synergistic action of the chemical liquid, a dense oxide film is formed on the surface of the electrode foil, thereby increasing the capacity of the capacitor and reducing the ESR value.
The preparation process of aluminum electrolytic capacitors is simplified, the ESR value is reduced, the capacitance capacity is improved, and the high-performance needs of electronic and electrical equipment are met.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and more specifically, to an aluminum electrolytic capacitor with reduced ESR and a preparation method thereof. Background Art
[0002] Aluminum electrolytic capacitors are capacitors with aluminum foil as electrodes, aluminum oxide film as dielectric layer, and electrolyte or solid electrolyte as electrolyte. Aluminum electrolytic capacitors have the advantages of large capacity, small size, and high reliability, and are widely used in electronic circuits.
[0003] Solid aluminum electrolytic capacitors are mainly composed of anode aluminum foil, cathode aluminum foil, solid electrolyte and shell. They use the oxide film formed on the surface of the aluminum foil as a dielectric, and conduct charge between the positive and negative electrodes through the solid electrolyte to achieve the charging and discharging function of the capacitor. The production process of solid aluminum electrolytic capacitors mainly includes core package production, core package fixation, formation, impregnation, polymerization, assembly waisting, aging, etc. Among them, the formation and impregnation treatment steps can activate the electrochemical properties of the capacitor, which plays a vital role in the capacitor's capacity, ESR (equivalent series resistance) and life.
[0004] The prior art chemical step is to immerse the nailed and rolled element into a chemical solution for chemical repair treatment. The chemical solution usually adopts an aqueous solution of one or more inorganic acids mixed in a certain ratio, such as phosphoric acid, boric acid, ammonium dihydrogen phosphate and phosphoric acid, ammonium citrate and phosphoric acid, etc. For example, a new chemical method for aluminum electrolytic capacitor anode foil disclosed in Chinese patent document 202310919107.5 includes the following steps: Step 1, first place the aluminum foil after corrosion treatment in pure water at a temperature of 95°C or above, and immerse it in After soaking for 5 to 12 minutes, the aluminum foil is placed in a first aqueous solution composed of ammonium adipate, adipic acid, sodium hypophosphite and boric acid for chemical formation. The voltage output waveform is an asymmetric waveform. The voltage amplitude is controlled to be 0 to 1000V, the current is 0 to 3000A, and the time is 1 to 999S. The number of periodic cycles is 1 to 1000 times. The pH value of the first aqueous solution is 4 to 5, the conductivity is 4000 to 5000μS / cm, and the chemical formation temperature is 85°C to 90°C to obtain a first-level chemically formed aluminum foil. The chemical formation process is complicated, and the ESR value of the obtained aluminum electrolytic capacitor is too large and the capacitance is too low, which cannot meet the needs of increasingly advanced electronic and electrical equipment.
[0005] Generally, the core impregnation treatment of aluminum electrolytic capacitors needs to be carried out under vacuum conditions, and the impregnation process is complicated. For example, Chinese patent application 202210906716.2 discloses an aluminum electrolytic capacitor core impregnation method, which includes S1: filling a tray with capacitor core packages; S2: placing the tray filled with core packages into an empty vacuum impregnation tank, and heating the vacuum impregnation tank so that the core package temperature reaches a predetermined temperature; S3: injecting electrolyte into the vacuum impregnation tank to a specified liquid level; S4: filling the vacuum impregnation tank with electrolyte; S5: filling the vacuum impregnation tank with electrolyte; S6: filling the vacuum impregnation tank with electrolyte; S7: filling the vacuum impregnation tank with electrolyte; S8: filling the vacuum impregnation tank with electrolyte; S9: filling the vacuum impregnation tank with electrolyte; S10: filling the vacuum impregnation tank with electrolyte; S11: filling the vacuum impregnation tank with electrolyte; S12: filling the vacuum impregnation tank with electrolyte; S13: filling the vacuum impregnation tank with electrolyte; S14: filling the vacuum impregnation tank with electrolyte; S15: filling the vacuum impregnation tank with electrolyte; S16: filling the vacuum impregnation tank with electrolyte; S17: filling the vacuum impregnation tank with electrolyte; S18: filling the vacuum impregnation tank with electrolyte; S19: filling the vacuum impregnation tank with electrolyte; S20: filling the vacuum impregnation tank with electrolyte; S21: filling the vacuum impregnation tank with electrolyte; S22: filling the vacuum impregnation tank with electrolyte; S23: filling the vacuum impregnation tank with electrolyte; S24: filling the vacuum impregnation tank with electrolyte; S25: filling the vacuum impregnation tank with electrolyte; The immersion tank is evacuated to vacuum, and the state of the electrolyte is observed through a transparent window. If the electrolyte boils, the process stops; S5: After the impregnation time requirement is reached, the vacuum state of the vacuum impregnation tank is released; S6: After continuous impregnation reaches the vacuum release time, positive pressure is applied to the vacuum impregnation tank until the pressurization time is met, the positive pressure is released, and the electrolyte in the vacuum impregnation tank is released; S7: Steps S3-S6 are repeated to achieve multiple impregnations; S8: After the impregnation is completed, the vacuum impregnation tank is evacuated to vacuum for vacuum dehydration. The impregnation process is complicated and cumbersome, and the production efficiency is low.
[0006] Therefore, there is an urgent need to provide a preparation method for aluminum electrolytic capacitors with simple process and low ESR and large capacitance. Summary of the invention
[0007] Based on this, it is necessary to provide an aluminum electrolytic capacitor with reduced ESR and a preparation method thereof in order to solve the above technical problems.
[0008] In order to solve the above technical problems, the present invention provides an aluminum electrolytic capacitor with reduced ESR and a preparation method thereof, which adopts the following technical solution:
[0009] A first aspect of the present invention provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, comprising the following steps:
[0010] S1, the anode foil and the cathode foil are separated by electrolytic paper and wound into a core package;
[0011] S2, core package fixed;
[0012] S3, immersing the fixed core package in a chemical solution for chemical formation;
[0013] S4, the core comprises an electrolyte monomer solution;
[0014] S5, placing the impregnated core package described in S4 into an oven for drying and polymerization;
[0015] S6, assemble the waist;
[0016] S7, aging;
[0017] The chemical forming liquid is composed of the following components by mass percentage: 5% to 15% of diacid salt, 1% to 7% of silane coupling agent containing 3 to 17 fluorine atoms, 0.5% to 3% of fluorine-containing nonionic surfactant, and 75% to 93.5% of solvent.
[0018] Furthermore, the dicarboxylic acid salt is any one of ammonium oxalate, ammonium hydrogen oxalate or ammonium dihydrogen phosphate.
[0019] Furthermore, the silane coupling agent containing 3 to 17 fluorine atoms is any one of trifluoropropylmethyldimethoxysilane, nonafluorohexyltrimethoxysilane or heptadecafluorodecyltriethoxysilane.
[0020] Furthermore, the fluorine-containing nonionic surfactant is any one of perfluorohexylethyl acrylate, FS-3100 and GS-FC368.
[0021] Furthermore, the solvent is a mixture of anhydrous ethanol and water, and the mass ratio of anhydrous ethanol to water is 1:1-10.
[0022] Furthermore, the chemical formation step comprises immersing the core package in a chemical formation liquid at 40-80° C., performing a direct current chemical formation treatment, and then cleaning and baking.
[0023] Furthermore, the voltage of the direct current is 0.75 to 1.3 times the rated voltage, and the time of the chemical formation treatment is 20 to 120 minutes.
[0024] Furthermore, the core package is baked at a temperature of 100 to 250° C. and a baking time of 30 to 180 minutes after formation.
[0025] Furthermore, the formation in step 3 is carried out under normal pressure; the monomer solution in step S4 is a thiophene or thiophene derivative solution, and the oxidant solution is an iron p-toluenesulfonate solution.
[0026] A second aspect of the present invention provides an aluminum electrolytic capacitor prepared by any of the above preparation methods.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The preparation method of the aluminum electrolytic capacitor with reduced ESR provided by the present invention has simpler steps, and the impregnation process does not need to be carried out in a vacuum state. A specific chemical forming liquid is selected, and a dense oxide film is formed on the surface of the electrode foil through the synergistic effect of the diacid salt, the silane coupling agent containing 3 to 17 fluorine atoms and the fluorine-containing non-ionic surfactant in the chemical forming liquid, thereby increasing the capacity of the capacitor and reducing the ESR value.
[0029] In the chemical formation liquid provided by the present invention, a fluorine-containing silane coupling agent reacts with anhydrous ethanol to generate silanol, and then the silanol combines with the hydroxyl group of the hydrated aluminum oxide film to modify the hydrated aluminum oxide; the surface tension of the solution is reduced by a fluorine-containing nonionic surfactant, and the attachment area of the silanol and the hydroxyl group of the hydrated aluminum oxide film is increased; during impregnation, an electric current is applied under acidic conditions to promote the conversion of the hydrated aluminum oxide film into a dense porous aluminum oxide film, and the content of the hydrated aluminum oxide is reduced, so that the monomer oxidant impregnation is easier to penetrate into the core package, the chemical formation liquid has stronger adhesion and better permeability, and is easier to penetrate into the cavities of the aluminum foil to react with it, the chemical formation step only needs to be completed once, and a better chemical formation effect can be achieved without the need for traditional cyclic chemical formation, and the impregnation step of the treated core package does not need to be carried out under vacuum, thereby simplifying the preparation process of the traditional aluminum electrolytic capacitor. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0031] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below.
[0032] Embodiment 1
[0033] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which comprises the following steps:
[0034] S1. Production of core package: the anode foil and cathode foil are separated by electrolytic paper and wound into a core package;
[0035] S2. Fixing the core package: fix the positive electrode guide pin of the core package on a fixing bar and place the fixing bar on the carrier;
[0036] S3. Formation: Immerse the core package in a 40°C forming solution and pass 0.75 times the rated voltage for 20 minutes, clean it for 1 minute after formation, and bake it at 100°C for 30 minutes after cleaning;
[0037] S4. Impregnation: The core package is immersed in the monomer solution for 2 to 3 minutes, and then placed in an oven for drying at a drying temperature of 55 to 65 ° C, and then the core package is immersed in an oxidant solution; In this step, the monomer solution used is a solution of thiophene or a thiophene derivative, and the oxidant solution is an iron toluenesulfonate solution;
[0038] S5 polymerization: The impregnated core package S4 is placed in an oven for drying and polymerization, the polymerization temperature is 90 to 110 ℃;
[0039] S6. Assemble the waist;
[0040] S7. Aging;
[0041] The chemical forming solution in this embodiment is composed of the following components by mass percentage: 5% ammonium oxalate, 1% trifluoropropylmethyldimethoxysilane, 0.5% perfluorohexylethyl acrylate, and 93.5% solvent;
[0042] The solvent is a mixture of anhydrous ethanol and water, and the mass ratio of anhydrous ethanol to water is 1:10;
[0043] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 1 was subjected to an initial performance test using a standard test method. The results are shown in Table 1 below:
[0044]
[0045] Embodiment 2
[0046] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in step S3:
[0047] S3. Formation: Immerse the core package in a 60°C forming solution and pass 1.1 times the rated voltage for 70 minutes, clean it for 10 minutes after formation, and bake it at 170°C for 100 minutes after cleaning;
[0048] The chemical forming liquid is composed of the following components by mass percentage: 10% ammonium oxalate, 4% trifluoropropylmethyldimethoxysilane, 1.5% perfluorohexylethyl acrylate, and 85.5% solvent;
[0049] The solvent is a mixture of anhydrous ethanol and water, and the mass ratio of anhydrous ethanol to water is 1:5.
[0050] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 2 was subjected to an initial performance test using a standard test method. The results are shown in Table 2 below:
[0051]
[0052] Embodiment 3
[0053] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in step S3:
[0054] S3. Formation: Immerse the core package in a forming solution at 80°C and pass 1.3 times the rated voltage for 120 minutes, clean it for 20 minutes after formation, and bake it at 250°C for 180 minutes after cleaning;
[0055] The chemical forming solution in this embodiment is composed of the following components by mass percentage: 15% ammonium oxalate, 7% trifluoropropylmethyldimethoxysilane, 3% perfluorohexylethyl acrylate, and 75% solvent;
[0056] The solvent is a mixture of anhydrous ethanol and water, and the mass ratio of anhydrous ethanol to water is 1:1.
[0057] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 3 was subjected to initial performance testing using a standard testing method. The results are shown in Table 3 below:
[0058]
[0059] Embodiment 4
[0060] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in that the dicarboxylic acid salt in the chemical formation solution in step S3 is ammonium hydrogen oxalate;
[0061] Specifically, the chemical conversion solution in this embodiment is composed of the following components by mass percentage: 5% ammonium hydrogen oxalate, 1% trifluoropropylmethyldimethoxysilane, 0.5% perfluorohexylethyl acrylate, and 93.5% solvent.
[0062] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 4 was subjected to initial performance testing using a standard testing method. The results are shown in Table 4 below:
[0063]
[0064] Embodiment 5
[0065] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment in that the diacid salt of the chemical forming solution in step S3 is ammonium hydrogen oxalate;
[0066] Specifically, the chemical conversion solution in this embodiment is composed of the following components by mass percentage: 10% ammonium hydrogen oxalate, 4% trifluoropropylmethyldimethoxysilane, 1.5% perfluorohexylethyl acrylate, and 85.5% solvent.
[0067] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 5 was subjected to initial performance testing using a standard testing method. The results are shown in Table 5 below:
[0068]
[0069] Embodiment 6
[0070] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the third embodiment in that the dicarboxylic acid salt in the chemical forming solution in step S3 is ammonium hydrogen oxalate;
[0071] Specifically, the chemical conversion solution in this embodiment is composed of the following components by mass percentage: 15% ammonium hydrogen oxalate, 7% trifluoropropylmethyldimethoxysilane, 3% perfluorohexylethyl acrylate, and 75% solvent.
[0072] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 6 was subjected to initial performance testing using a standard testing method. The results are shown in Table 6 below:
[0073]
[0074] Embodiment 7
[0075] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in that the diacid salt of the chemical forming solution in step S3 is diammonium dihydrogen phosphate;
[0076] Specifically, the chemical forming solution in this embodiment is composed of the following components by mass percentage: 5% diammonium dihydrogen phosphate, 1% trifluoropropylmethyldimethoxysilane, 0.5% perfluorohexylethyl acrylate, and 93.5% solvent.
[0077] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 7 was subjected to initial performance testing using a standard testing method. The results are shown in Table 7 below:
[0078]
[0079] Embodiment 8
[0080] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment in that the diacid salt of the chemical forming solution in step S3 is ammonium dihydrogen phosphate;
[0081] Specifically, the chemical forming solution in this embodiment is composed of the following components by mass percentage: 10% diammonium phosphate, 4% trifluoropropylmethyldimethoxysilane, 1.5% perfluorohexylethyl acrylate, and 85.5% solvent;
[0082] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 8 was subjected to initial performance testing using a standard testing method. The results are shown in Table 8 below:
[0083]
[0084] Embodiment 9
[0085] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the third embodiment in that the diacid salt of the chemical forming solution in step S3 is diammonium dihydrogen phosphate;
[0086] Specifically, the chemical forming solution in this embodiment is composed of the following components by mass percentage: 15% ammonium dihydrogen phosphate, 7% trifluoropropylmethyldimethoxysilane, 3% perfluorohexylethyl acrylate, and 75% solvent;
[0087] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 9 was subjected to initial performance testing using a standard testing method. The results are shown in Table 9 below:
[0088]
[0089] Embodiment 10
[0090] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is nonafluorohexyltrimethoxysilane, and the fluorine-containing nonionic surfactant is the fluorine surfactant FS-3100 produced by DuPont (hereinafter referred to as FS-3100);
[0091] Specifically, the chemical forming solution in this embodiment is composed of the following components by mass percentage: 5% ammonium oxalate, 1% nonafluorohexyltrimethoxysilane, 0.5% FS-3100, and 93.5% solvent;
[0092] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 10 was subjected to initial performance testing using a standard testing method. The results are shown in Table 10 below:
[0093]
[0094] Embodiment 11
[0095] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is nonafluorohexyltrimethoxysilane, and the fluorine-containing nonionic surfactant is FS-3100;
[0096] Specifically, the chemical formation solution described in this embodiment is composed of the following components by mass percentage: 10% ammonium oxalate, 4% nonafluorohexyltrimethoxysilane, 1.5% FS-3100, and 85.5% solvent;
[0097] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 11 was subjected to initial performance testing using a standard testing method. The results are shown in Table 11 below:
[0098]
[0099] Embodiment 12
[0100] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the third embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is nonafluorohexyltrimethoxysilane, and the fluorine-containing nonionic surfactant is FS-3100;
[0101] Specifically, the chemical forming solution described in this embodiment is composed of the following components by mass percentage: 15% ammonium oxalate, 7% nonafluorohexyltrimethoxysilane, 3% FS-3100, and 75% solvent;
[0102] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 12 was subjected to initial performance testing using a standard testing method. The results are shown in Table 12 below:
[0103]
[0104] Embodiment 13
[0105] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the first embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is heptadecafluorodecyltriethoxysilane, and the fluorine-containing nonionic surfactant is GS-FC368 (purchased from Shanghai Zicheng International Trade Co., Ltd.);
[0106] Specifically, the chemical forming solution in this embodiment is composed of the following components by mass percentage: 5% ammonium oxalate, 1% heptadecafluorodecyltriethoxysilane, 0.5% GS-FC368, and 93.5% solvent;
[0107] The 220 μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 13 was subjected to initial performance testing using a standard testing method. The results are shown in Table 13 below:
[0108]
[0109] Embodiment 14
[0110] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is heptadecafluorodecyltriethoxysilane, and the fluorine-containing nonionic surfactant is GS-FC368;
[0111] Specifically, the chemical forming solution of this embodiment is composed of the following components by mass percentage: 10% ammonium oxalate, 4% heptadecafluorodecyltriethoxysilane, 1.5% GS-FC368, and 85.5% solvent;
[0112] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 14 was subjected to initial performance testing using a standard testing method. The results are shown in Table 14 below:
[0113]
[0114] Embodiment 15
[0115] This embodiment provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the third embodiment in that the silane coupling agent with 3 to 17 fluorine atoms in the chemical forming solution in step S3 is heptadecafluorodecyltriethoxysilane, and the fluorine-containing nonionic surfactant is GS-FC368;
[0116] Specifically, the chemical forming solution of this embodiment is composed of the following components by mass percentage: 15% ammonium oxalate, 7% heptadecafluorodecyltriethoxysilane, 3% GS-FC368, and 75% solvent;
[0117] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Example 15 was subjected to initial performance testing using a standard testing method. The results are shown in Table 15 below:
[0118]
[0119] Comparative Example 1
[0120] This comparative example provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment in that the chemical forming solution in step S3 is composed of the following components by mass percentage: 10% ammonium oxalate, 90% solvent;
[0121] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Comparative Example 1 was subjected to initial performance testing using standard testing methods. The results are shown in Table 16 below:
[0122]
[0123] The chemical forming liquid used in Comparative Example 1 does not contain a silane coupling agent containing 3 to 17 fluorine atoms and a fluorine-containing nonionic surfactant. The capacity of the obtained aluminum electrolytic capacitor is about 15% lower than that of the capacitors prepared by the methods of Examples 1 to 15, and the ESR value is increased by more than 20%.
[0124] Comparative Example 2
[0125] This comparative example provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment only in that the silane coupling agent containing 3 to 17 fluorine atoms is replaced by the fluorine-free silane coupling agent A-171 in the chemical forming liquid in step S3;
[0126] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Comparative Example 2 was subjected to initial performance testing using standard testing methods. The results are shown in Table 17 below:
[0127]
[0128] Comparative Example 3
[0129] This comparative example provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from Example 2 in that boric acid is used instead of a diacid salt in the chemical forming solution in step S3;
[0130] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of Comparative Example 3 was subjected to initial performance testing using standard testing methods. The results are shown in Table 18 below:
[0131]
[0132] Comparative Example 4
[0133] This comparative example provides a method for preparing an aluminum electrolytic capacitor with reduced ESR, which differs from the second embodiment only in that the conventional anionic surfactant sodium dodecylbenzene sulfonate is used in place of the fluorine-containing nonionic surfactant in the chemical forming solution in step S3;
[0134] The 220μF 6.3V aluminum electrolytic capacitor prepared by the method of comparative example 3 was subjected to initial performance testing using standard testing methods. The results are shown in Table 19 below:
[0135]
[0136] Compared with the results of Example 2, the test results of Comparative Examples 2 to 4 show a significant decrease in CAP values, while both ESR values and LC values increase by more than 20%. In Example 2, a fluorinated silane coupling agent, a diacid solution, and a fluorinated nonionic surfactant are used in a coordinated reaction to generate dense and porous alumina, thereby improving the overall performance of the final aluminum electrolytic capacitor.
[0137] Obviously, the embodiments described above are only a part of the embodiments of the present application, rather than all of the embodiments. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the present application specification, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of the present application.
Claims
1. A method for preparing an aluminum electrolytic capacitor with reduced ESR, characterized in that: The following steps are involved: S1, the anode foil and the cathode foil are separated by electrolytic paper and wound into a core package; S2, core package fixed; S3, immersing the fixed core package in a chemical solution for chemical formation; S4, the core comprises an electrolyte monomer solution; S5, placing the impregnated core package described in S4 into an oven for drying and polymerization; S6, assemble the waist; S7, aging; The chemical forming liquid is composed of the following components by mass percentage: 5% to 15% of diacid salt, 1% to 7% of silane coupling agent containing 3 to 17 fluorine atoms, 0.5% to 3% of fluorine-containing nonionic surfactant, and 75% to 93.5% of solvent.
2. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 1, characterized in that: The dicarboxylic acid salt is any one of ammonium oxalate, ammonium hydrogen oxalate and ammonium dihydrogen phosphate.
3. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 1, characterized in that: The silane coupling agent containing 3 to 17 fluorine atoms is any one of trifluoropropylmethyldimethoxysilane, nonafluorohexyltrimethoxysilane or heptadecafluorodecyltriethoxysilane.
4. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 1, characterized in that: The fluorine-containing nonionic surfactant is any one of perfluorohexylethyl acrylate, FS-3100 and GS-FC368.
5. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 2, characterized in that: The solvent is a mixture of anhydrous ethanol and water, and the mass ratio of anhydrous ethanol to water is 1:1-10.
6. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 1, characterized in that: The chemical formation step comprises immersing the core package in a chemical formation liquid at 40-80° C., performing direct current chemical formation treatment, cleaning the core package, and baking the core package after cleaning.
7. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 5, characterized in that: The voltage of the direct current is 0.75 to 1.3 times the rated voltage, and the time of the chemical formation treatment is 20 to 120 minutes.
8. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 5, characterized in that: The baking temperature of the core package after formation is 100-250°C, and the baking time is 30min-180min.
9. The method for preparing an aluminum electrolytic capacitor with reduced ESR according to claim 1, characterized in that: The formation in step 3 is carried out under normal pressure; the monomer solution in step S4 is a thiophene or thiophene derivative solution, and the oxidant solution is an iron p-toluenesulfonate solution.
10. An aluminum electrolytic capacitor prepared by the preparation method according to claims 1 to 9.
Citation Information
Patent Citations
Aluminum electrolytic capacitor core immersion method
CN115132504A
Novel formation method of aluminum electrolytic capacitor anode foil
CN116752198A